A influência da indústria na regulamentação Sulamericana: a defesa de interesses técnicos do setor de máquinas e equipamentos para manejo de áreas verdes na regulamentação de produtos - Reguly, Maria Cristina Werle (Universidade do Vale do Rio dos Sinos, 2015)
The participation of companies in the product regulation is a practice that exists for more than 30 years in Europe and United States. However, the interaction between government and industry in South America has singularities compared to the US and the European Union mainly due to socio-political and economic differences. The main focus of this work is the presentation of a framework with factors that guide the companies from a specific industrial sector to exert influence on the content of product regulations issued by the countries of South America. To achieve the goal it was started by the analysis of the determining factors on the business lobby regarding product regulations published by governments and regulators in the European Union and the USA. As next the presence and the applicability of these in the South American scenario were evaluated, showing that despite the presence of the factors the applicability requires adaptations. The use of design research as method provided, due to its prescriptive approach, an interaction between theory and praxis. The qualitative validation was performed through the evaluation by experts in the field using a semi-structured interview technique at two different times of the research. In addition, direct observation at meetings and participation in a workshop helped to highlight and enrich the knowledge on the subject. As a result a framework and the main factors to be observed in the influence process of firms when interacting with the policy makers of the South American countries is presented. This includes the establishment of an interest group. Due to time limitation of this Master program, the application of the propositions is not described.
Keywords: Defesa de interesses; Regulamentação de produtos; América do Sul; Lobby; Interest groups; Product regulation; South America; ACCNPQ::Ciências Sociais Aplicadas::Administração